Perancangan Sistem Informasi Geografis (SIG) untuk Pendataan Jaringan Kabel pada Area Distribusi - Aldi Huseini Milyanto; Arif Rahman Sujatmika; Budiman (UNIB Press, 2026)
This study focuses on the development of a Geographic Information System (GIS) designed to support the recording of cable network data in distribution areas. One of the main challenges encountered by network managers is the lack of an effective and accurate method for mapping the locations of network infrastructure. To address this issue, a web-based GIS is proposed to enable more structured processes of data recording, monitoring, and maintenance of poles and cable networks. The system development adopts a prototype-based approach, which includes requirement analysis, system modeling, implementation, and testing phases. The application is implemented using HTML, PHP, MySQL, and Leaflet.js as a digital mapping library. Spatial data are collected through field surveys and converted into geographic coordinates for visualization on an interactive map. The developed system is able to display pole locations and cable routes in real time, thereby supporting asset management and distribution network analysis. Overall, the system provides an effective solution for managing cable network infrastructure data.